Effects of water-channel attractions on single-file water permeation through nanochannels. (15th June 2016) - Xu, Yousheng; Tian, Xingling; Lv, Mei; Deng, Maolin; He, Bing; Xiu, Peng; Tu, Yusong; Zheng, Youqu
Abstract: Single-file transportation of water across narrow nanochannels such as carbon nanotubes has attracted much attention in recent years. Such permeation can be greatly affected by the water-channel interactions; despite some progress, this issue has not been fully explored. Herein we use molecular dynamics simulations to investigate the effects of water-channel attractions on occupancy, translational (transportation) and orientational dynamics of water inside narrow single-walled carbon nanotubes (SWNTs). We use SWNTs as the model nanochannels and change the strength of water-nanotube attractions to mimic the changes in the hydrophobicity/polarity of the nanochannel. We investigate the dependence of water occupancy inside SWNTs on the water-channel attraction and identify the corresponding threshold values for drying states, wetting-drying transition states, and stably wetting states. As the strength of water-channel attractions increases, water flow increases rapidly first, and then decreases gradually; the maximal flow occurs in the case where the nanochannel is predominately filled with the 1D water wire but with a small fraction of 'empty states', indicating that appropriate empty-filling (drying-wetting) switching can promote water permeation. This maximal flow is unexpected, since in traditional view, the stable and tight hydrogen-bonding network of the water wire is the prerequisite for high permeability of water. The underlying mechanism is discussed from an energetic perspective. In addition, the effect of water-channel attractions on reorientational dynamics of the water wire is studied, and a negative correlation between the flipping frequency of water wire and the water-channel attraction is observed. The underlying mechanism is interpreted in term of the axial total dipole moment of inner water molecules. This work would help to better understand the effects of water-channel attractions on wetting properties of narrow nanochannels, and on single-file water permeation through nanochannels, which might be helpful in designs of high-flux nanochannels.